Efficacy and safety of levilimab in combination with methotrexate in subjects with rheumatoid arthritis: Results of phase II AURORA study - V. I. Mazurov; E. G. Zotkin; I. Z. Gaydukova; E. P. Ilivanova; T. V. Kropotina; T. V. Plaksina; O. B. Nesmeyanova; N. F. Soroka; E. A. Kunder; E. A. Dokukina; Yu. N. Linkova; N. A. Kravtsova; et al. (Научно-практическая ревматология)
Levilimab (LVL) is a monoclonal antibody against the interleukin-6 receptor (IL6R). The article presents data obtained during 56 weeks of the AURORA phase II study.Objective: to evaluate the efficacy safety and immunogenicity of LVL in methotrexate (MTX) resistant patients with active rheumatoid arthritis (RA).Materials and methods. 105 patients with active RA were randomized in a 1:1:1 ratio into two LVL or placebo groups. LVL was administered subcutaneously at a dose of 162 mg every week (QW) or every other week (Q2W). All patients received MTX. After evaluating the primary endpoint of 20% improvement in ACR criteria (ACR20) at week 12, patients in the placebo group were switched to LVL Q2W. The study duration was 56 weeks. The frequency, profile, degree and severity of adverse events were determined in each group for safety assessment. The immunogenicity of LVL was determined by the proportion of patients with identified binding and neutralizing antidrug antibodies. Results. LVL in both regimens was superior to placebo. At week 12, the incidence of ACR20 achievement was 77.1% (LVL QW), 57.1% (LVL Q2W), and 17.1% (placebo) with 95% confidence intervals [37.53; 82.54] (p<0.0001) and [19.08; 68.42] (p=0.003) for the effect difference between LVL and placebo groups. The clinical response, more pronounced in the LVL QW group, persisted until week 52 with an increase in the proportion of patients with ACR50/70, low activity and RA remission. The most common treatment-related adverse events were laboratory abnormalities (predominantly grade 1–2) such as neutropenia, elevated alanine aminotransferase, aspartate aminotransferase levels, hypercholesterolemia, and elevated triglyceride levels. Antidrug antibodies were not identified.Conclusion. In MTX-resistant patients with active RA, the efficacy of both LVL regimens at a dose of 162 mg in combination with MTX was significantly superior to MT monotherapy. LVL QW lead to highest treatment response. LVL has been shown to be well tolerated and low immunogenicity. LVL safety profile is similar to IL6R inhibitors.